Sintesis protein mikrobia sapi perah peranakan friesian holstein yang diberi pakan basal rumput raja, jerami jagung dan jerami padi dengan suplementasi konsentrat protein tinggi=Rumen microbial protein synthesis ofHolste - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
ABSTRACT Fifteen Dairy cattle of Holstein Crossbred heifer were used for estimating rumen microbial protein synthesis. The cattle fed by a single diet of King Grass (KG), Corn Stover (CS) or rice straw (RS) ad libitum as basal diet that was supplemented by a high protein concentrate. Microbial protein synthesis were estimated from derivatives concentration. Data obtained: microbial protein synthesis (MPS) were analyzed using analyses of variance, in split plot and completely randomized design. The means differences were analyzed by DMRT. The result of this research showed that purin derivatives concentration of cattle fed on KG, CS, and RS were 75.07